Unpacking the Multidimensional Nature of EFL Speaking Difficulties: A Holistic Framework of Learner-Centered Needs - Chusni Hadiati; Usep Muttaqin; Nadia Gitya Yulianita; Rosdiana Puspita Sari (FKIP Universitas Lampung, 2026)
Unpacking the Multidimensional Nature of EFL Speaking Difficulties: A Holistic Framework of Learner-Centered Needs. Speaking is a critical yet challenging skill for EFL learners due to its spontaneous nature, real-time processing, and high emotional demands. This study explores the individual challenges that students face in learning to speak English and how these affect their classroom participation and language development. Objectives: The study aims to examine the challenges that students encounter while learning to speak English and how these challenges influence their classroom participation and language development. Methods: Drawing on key theories of communicative competence, the Affective Filter Hypothesis, and pragmatic competence, this research employed a qualitative descriptive design, including open-ended questionnaires and semi-structured interviews with 25 university students enrolled in a speaking class. Findings: Thematic analysis revealed five interrelated dimensions of difficulty: (1) linguistic challenges, especially vocabulary and grammar limitations; (2) psychological barriers, including anxiety, fear of negative evaluation, and lack of confidence; (3) the impact of classroom environment and activity design on comfort and performance; (4) learners’ topic preferences, where familiar and casual themes are favored over abstract or technical subjects; and (5) the importance of pedagogical support, such as collaborative tasks, smaller group settings, and constructive feedback. Conclusion: The findings underscore that speaking difficulties are not merely linguistic but are deeply influenced by affective and contextual factors. Students benefit most from interactive, low-pressure environments that allow gradual confidence-building. The study concludes by recommending a more student-centered approach to speaking instruction—one that acknowledges individual learner differences, promotes meaningful interaction, and fosters both communicative competence and psychological readiness. These insights can guide teachers in designing more inclusive and engaging speaking classes that empower learners to participate actively and confidently. Keywords: EFL speaking challenges, communicative competence, affective filter, classroom interaction, learner confidence.